2017
DOI: 10.1177/0899764017737382
|View full text |Cite
|
Sign up to set email alerts
|

Economic Consequences of Hiring an Auditor With Industry Expertise: An Empirical Analysis Among NPOs

Abstract: This study examines economic consequences of auditor choice in the Belgian nonprofit (NP) setting, where the identity of both the audit firm and the audit partner is required to be disclosed. Specifically, we examine the influence of auditor choice in favor of an auditor with industry expertise on future contributions (being the sum of donations and grants) received among a large sample of Belgian nonprofit organizations (NPOs). Consistent with a signaling perspective, our results indicate that NPOs benefit fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 66 publications
(101 reference statements)
0
15
0
Order By: Relevance
“…This split of the aggregate figure is derived from the notes to the financial statements. Prior research on Belgian data (see Reheul et al, 2018) reports considerable inaccuracies with regard to this split in the notes, and findings from this additional analysis should therefore be interpreted with caution. The interaction between donations and PREBELOW yields a significantly positive coefficient, whereas the coefficient for the interaction between grants and PREBELOW is insignificant.…”
Section: Additional Analysesmentioning
confidence: 83%
“…This split of the aggregate figure is derived from the notes to the financial statements. Prior research on Belgian data (see Reheul et al, 2018) reports considerable inaccuracies with regard to this split in the notes, and findings from this additional analysis should therefore be interpreted with caution. The interaction between donations and PREBELOW yields a significantly positive coefficient, whereas the coefficient for the interaction between grants and PREBELOW is insignificant.…”
Section: Additional Analysesmentioning
confidence: 83%
“…This allows for smaller audit firms focusing on nonprofit sector audits to become industry specialists in their geographic area. Similar to Reheul et al (2013) and Reheul et al (2018), we also consider the different industries within the nonprofit sector, as they likely require distinct and specialized knowledge. We use the NTEE classification system used by the Internal Revenue Service (IRS) and the National Center for Charitable Statistics (NCCS) to identify subindustries within the nonprofit sector.…”
Section: Methodsmentioning
confidence: 99%
“…Additional nonprofit research finds auditors specializing in nonprofit sector audits are associated with higher fees (Beattie, Goodacre, Pratt, & Stevenson, 2001; Fischer, Johnson, & Elder, 2004) and decreased internal control weakness reporting (Petrovits et al, 2011). Research on European nonprofits has found industry specialization associated with an increase in future government grants (Reheul et al, 2018), lower audit fees (Verbruggen et al, 2015), and longer audit report delays (Reheul et al, 2013). According to Reheul et al (2013), the positive association between auditor industry specialization and audit report lag is indicative of specialist auditors expending greater auditor effort to provide higher audit quality.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations